Management of unilateral head and neck carcinoma of unknown primary: Retrospective analysis of the impact of postoperative radiotherapy target volumes. Issue 2 (18th November 2019) - Podeur, Fabien; Pommier, Pascal; Crozes, Carole; Monchet, Elodie; Ton Van, Jean; Roux, Pierre‐Eric; Poupart, Marc; Zrounba, Philippe; Julieron, Morbize; Deneuve, Sophie
Abstract: Background: We compared the outcome of postoperative unilateral cervical nodes radiotherapy (UL‐RT) vs bilateral cervical nodes plus total mucosal irradiation (COMP‐RT) in the management of head and neck carcinoma of unknown primary (HNCUP). Methods: HNCUP, defined by the absence of primary despite a PET‐CT combined with a panendoscopy, were treated with curative intent by initial ipsilateral neck dissection. Sixty‐nine patients with unilateral HNCUP were included: 23 received UL‐RT while 46 received COMP‐RT. Carcinologic outcomes and long‐term quality of life (QOL) according to the QOL Questionnaire for Head and Neck 35 were assessed. Results: Within 6.3 years of median follow‐up, there was no significant difference in primary tumor emergence rate ( P = .68), cervical node recurrence rate ( P = .34), or overall survival ( P = .33) between UL‐RT and COMP‐RT groups. A trend toward QOL improvement was observed in the UL‐RT group. Conclusion: UL‐RT seems to provide similar outcomes as COMP‐RT in unilateral HNCUP management.